2006
DOI: 10.1007/s00330-006-0465-1
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo flow simulation in coronary arteries based on computed tomography datasets: feasibility and initial results

Abstract: The purpose of this paper was to non-invasively assess hemodynamic parameters such as mass flow, wall shear stress (WSS), and wall pressure with computational fluid dynamics (CFD) in coronary arteries using patient-specific data from computed tomography (CT) angiography. Five patients (two without atherosclerosis, three with atherosclerosis) underwent retrospectively electrocardiogram (ECG) gated 16-detector row CT using ECG-pulsing and geometric models of coronary arteries were reconstructed for CFD analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…For a similar study, Pivkin et al, 2005 used a sinusoidal velocity waveform. Other investigations have defined steady state boundary conditions (Soulis et al, 2006) or used a reference waveform from previous literature (Frauenfelder et al, 2007;Glor et al, 2003;Johnston et al, 2006). Few studies have paired in vivo geometries with corresponding in vivo flow.…”
Section: In Vivo Coronary Artery Studymentioning
confidence: 99%
“…For a similar study, Pivkin et al, 2005 used a sinusoidal velocity waveform. Other investigations have defined steady state boundary conditions (Soulis et al, 2006) or used a reference waveform from previous literature (Frauenfelder et al, 2007;Glor et al, 2003;Johnston et al, 2006). Few studies have paired in vivo geometries with corresponding in vivo flow.…”
Section: In Vivo Coronary Artery Studymentioning
confidence: 99%
“…Some assumed the blood flow in coronary arteries to be laminar (7)(8)(9)(10)(11)(12)(13)(14) and behave as Newtonian fluid (8,(15)(16)(17) and some studied turbulence transition and non-Newtonian effects considering idealized straight arterial model with single model stenosis obstruction (11,15,(17)(18)(19)(20)(21). Several experimental investigations have been carried out on flow disturbances in the downstream region of idealized modeled stenosis (18,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…86) Recently, it is reported that endothelial shear stress can be evaluated by CCTA. [87][88][89][90] Plaque may be assessed by adding physiological information such as FFR and shear stress more comprehensively. As the result, plaque vulnerability could be evaluated more accurately.…”
Section: Problem In Plaque Evaluation By Cctamentioning
confidence: 99%